Performance Evaluation Systems and Budgetary Slack in Chinese Universities: The Moderating Effect of Financial Transparency - Gao, Jie; Yaacob, Zulnaidi (International Review of Management and Marketing, 2026)
Chinese universities increasingly operate under performance-oriented funding regimes with tighter fiscal constraints and stronger accountability requirements. These conditions may lead to budgetary slack when budget holders possess private information relative to central finance offices. This article investigates whether performance evaluations reduce budgetary slack, both directly and by promoting financial transparency. It also examines if transparency makes these evaluations more effective at reducing slack. This study employed a quantitative, cross-sectional survey design in Chinese universities. A bilingual (English–Chinese) questionnaire using a five-point Likert scale was administered to personnel involved in budgeting and financial management (central finance office staff, school/college administrators, department heads, and research administration personnel). A total of 400 valid responses were analyzed using partial least squares structural equation modelling (PLS-SEM) with bootstrapping (5,000 resamples). The PLS-SEM results indicate that performance evaluation systems are positively associated with financial transparency and negatively associated with budgetary slack. Financial transparency is also negatively related to slack and significantly strengthens the slack-reducing effect of performance evaluation systems. Overall, the model explains a substantial proportion of variance in budgetary slack (R2 = 0.347), and the measures demonstrate satisfactory reliability as well as convergent and discriminant validity. The study integrates management control and public-sector transparency perspectives by modelling financial transparency as both a governance mechanism and a boundary condition for the effectiveness of performance evaluation. Practically, performance-oriented budgeting reforms are unlikely to curb slack if transparency of allocation rules, execution reports, and adjustment rationales remains weak.